A clinical study on association between hearing loss and inflammatory bowel disease in a population attending a hospital - Akhter, Mymoona; Rehman, Ayaz; Kadla, Showkat; Hamid, Sajad; Najeeb, Qazi; Makdoomi, Mohd Arif; Mughal, Basharat (International Journal of Research in Medical Sciences, 2017)
Background: Inflammatory bowel disease usually presents with gastrointestinal stigmata of weight loss, anaemia, and rectal bleeding, but may exhibit prominent extra-intestinal manifestations also such as joint symptoms, skin signs and some other auto-immune manifestations. During the last few years many authors have reported serious complications of IBD manifesting in the Ear-Nose-Throat (ENT) and influencing disease morbidity. Methods: Twenty four patients with active ulcerative colitis (mean age 45 years) were recruited prospectively along with 24 healthy age- and sex-matched controls. Otoscopy, tympanometry and pure tone audiometry were performed. Otoscopy and tympanometry were normal in all patients and controls. Pure tone audiometry showed sensorineural hearing loss over all frequencies in patients with inflammatory bowel disease and compared with controls. The otologic data including age of onset, family history of otologic problems, exposure to noise and audiometric findings were also reviewed. Results: Out of 48 patients with a history of IBD, 24 had documented SNHL, 17 of these patients had a diagnosis of ulcerative colitis and 7 had Crohn’s disease. 22 patients had bilateral SNHL, and 2 patients had unilateral SNHL. Tinnitis were the most common associated aural complaint. Conclusion: Sensorineural hearing loss is very unusual finding, possibly of auto-immune aetiology. We recommend steroid or immunosuppressive therapy in such a patient. Evidence for an autoimmune basis for this condition is reviewed and the potential benefit of systemic corticosteroids emphasized.